AGRIBUSINESS INNOVATION IN FRESHWATER SWAMP THROUGH DEVELOPMENT OF ORGANIC RICE - Fauzi, Muhammad (TROPICAL WETLAND JOURNAL, 2016)
In the economy of South Kalimantan, the agricultural sector has a significant growth and plays a role as one of the major contributors to the economic structure. However, in some areas with particular land typology like freshwater swamp; it is not reflected in the level of farmers’ welfare. In reality, many farming households in freshwater swamp that solely rely on rice farming still live in a poor condition because of low income. It is therefore necessary to find the alternative solutions through agribusiness innovation. Until now freshwater swamp is always identified with non-organic rice or conventional freshwater swamp rice; Alabio livestock, Alabio potato and Swamp buffalo. The purpose of this study was to analyze the potency of freshwater swamp for the welfare of farmers through agribusiness innovation in addition to oil palm plantations. The study was conducted in Teluk Limbung Village, Babirik Subdistrict, Hulu Sungai Utara Regency, by census with 17 farmers as the respondents. The productivity of organic rice in freshwater swamp reached 4.6 tons/ha. The earned income was greater compared to the income when the farmers only grew inorganic rice like what is commonly cultivated by farmers in the swampy lands.